Pengaruh Karakter Serta Keprofesionalan Dosen dalam Proses Perkuliahan Guna Menjadikan Mahasiswa yang Cerdas dan Kritis - Muhammad Fahmi Alfarisi (ScienceEdu: Jurnal Pendidikan IPA, 2019)
Lectures are attended by students and lecturers as facilitators. The success or failure of the lecture process can be measured by the ability of students, both their intellectual abilities and other abilities. The increase of students 'intellectual ability in their fields other than by doing individual learning such as diligent reading and others, the attitude and professionalism of lecturers who teach them is also very influential on students' intellectual development, such as having a teaching strategy that can give students an incentive to think critically and others. However, even though students have high intelligence, the lecturers who teach are not professional, so the lecture process will not last maximally even though the lecturer is only a facilitator.